1993
DOI: 10.1115/1.2895494
|View full text |Cite
|
Sign up to set email alerts
|

Viscosity Sensing With Lamb-Wave Microsensor: Dimethylsulfoxide Solution Viscosity as a Function of Temperature

Abstract: Recently, a new microsensor employing low-velocity ultrasonic Lamb waves was developed and demonstrated to be capable of measuring the viscosity of solutions in small volumes. The microsensor, when attached to a temperature-controlled stage, can measure viscosity as a function of temperature. In this investigation, the ultrasonic Lamb-wave oscillator is employed to experimentally measure the viscosity of dimethylsulfoxide (Me2SO) solutions as a function of temperature. The microsensor and the experimental proc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(4 citation statements)
references
References 0 publications
1
3
0
Order By: Relevance
“…A simple stereological analysis was performed using NIH™ image analysis software (NIH, Bethesda, MD) to estimate the initial radius of the ice crystals, R( ) 0 at the phase change temperature ( T ph0 ). We found that the initial radius of the ice crystals are ~2.7 ± 0.1 and ~3.7 ± 0.05 times smaller in the 5x and 10x PBS solution than in the 1x PBS 3 The viscosity (µ) model used in the present study predicts a ten fold increase in the value of µ between 0˚C and -40 ˚C which correlates reasonably well with the measured values [47]. Other viscosity models [48,49] also predict a similar increase over the temperature range of interest.…”
Section: R R Rsupporting
confidence: 83%
See 2 more Smart Citations
“…A simple stereological analysis was performed using NIH™ image analysis software (NIH, Bethesda, MD) to estimate the initial radius of the ice crystals, R( ) 0 at the phase change temperature ( T ph0 ). We found that the initial radius of the ice crystals are ~2.7 ± 0.1 and ~3.7 ± 0.05 times smaller in the 5x and 10x PBS solution than in the 1x PBS 3 The viscosity (µ) model used in the present study predicts a ten fold increase in the value of µ between 0˚C and -40 ˚C which correlates reasonably well with the measured values [47]. Other viscosity models [48,49] also predict a similar increase over the temperature range of interest.…”
Section: R R Rsupporting
confidence: 83%
“…However, a decrease in viscosity (or an increase in diffusivity, D 2 ) with increasing solute is contrary to published literature [47][48][49]. Therefore, the decrease in ν 2 with increasing concentration of solutes must be due to the reduction in R (as suggested by cryomicroscopy images shown in Fig.…”
Section: Magnitude Of Latent Heat Releasementioning
confidence: 69%
See 1 more Smart Citation
“…[52][53][54] These processes can significantly benefit acoustofluidic lab-on-a-chip systems 55 due to their high degree of reproducibility, essential for consistent acoustic actuation, and low-cost batch fabrication. Thin-film transducers are compatible with most of the acoustophoretic methods deployed with their bulk piezoelectric counterparts, such as patterning, 56,57 sensing 44,58,59 and streaming generation. 44,[60][61][62] However, the thin films can be deposited onto microfabricated features, enabling new actuation methods that were previously impossible.…”
Section: Ultrasonicmentioning
confidence: 99%